Large-scale structure-informed multiple sequence alignment of proteins with SIMSApiper - Crauwels, Charlotte; Heidig, Sophie-Luise; Díaz, Adrián; Vranken, Wim F (Bioinformatics (Oxford, England), 2024)
Summary SIMSApiper is a Nextflow pipeline that creates reliable, structure-informed MSAs of thousands of protein sequences faster than standard structure-based alignment methods. Structural information can be provided by the user or collected by the pipeline from online resources. Parallelization with sequence identity-based subsets can be activated to significantly speed up the alignment process. Finally, the number of gaps in the final alignment can be reduced by leveraging the position of conserved secondary structure elements. Availability and implementation The pipeline is implemented using Nextflow, Python3, and Bash. It is publicly available on github.com/Bio2Byte/simsapiper.